Proposed role of ATP in protein breakdown: conjugation of protein with multiple chains of the polypeptide of ATP-dependent proteolysis. - Hershko, A (1980)
The heat-stable polypeptide ATP-dependent proteolysis factor 1 (APF-1) of the reticulocyte proteolytic system forms covalent compounds with proteins in an ATP-requiring reaction. APF-1 and lysozyme, a good substrate for ATP-dependent proteolysis, form multiple conjugates, as was shown by comigration of label from each upon gel electrophoresis. Multiple bands were also seen with other substrates of the ATP-dependent proteolytic system, such as globin or alpha-lactalbumin. Analysis of the ratio of APF-1 to lysozyme radioactivities and of the molecular weights of the bands indicated that they consist of increasing numbers of the APF-1 polypeptide bound to one molecule of lysozyme. The covalent linkage is probably of an isopeptide nature, because it is stable to hydroxylamine and alkali, and polylysine is able to give conjugates of APF-1. Removal of ATP after formation of the 125I-labeled APF-1 conjugates with endogenous proteins caused the regeneration of APF-1, indicating presence of an amidase. This reaction is thought to compete with proteases that may act on APF-1-protein conjugates, especially those containing several APF-1 ligands. A sequence of reactions in which the linkage of APF-1 to the substrate is followed by the proteolytic breakdown of the substrate is proposed to explain the role of ATP.